2022
DOI: 10.3390/cancers14153773
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Abiraterone versus Enzalutamide for Prostate Cancer: A Scoping Review

Abstract: Abiraterone acetate (AA) and enzalutamide (ENZ) are commonly used for metastatic prostate cancer. It is unclear how their outcomes and toxicities vary with patient-specific factors because clinical trials typically exclude patients with significant comorbidities. This study aims to fill this knowledge gap and facilitate informed treatment decision making. A registered protocol utilizing PRISMA scoping review methodology was utilized to identify real-world studies. Of 433 non-duplicated publications, 23 were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Additionally, a comprehensive systematic review of realworld studies found few literature reviews on cardiovascular events [10]. Shah et al found more pronounced cardiovascular events in patients using AA than ENZ therapy [10]; however, some of the articles identified included research populations with pre-existing cardiovascular conditions [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, a comprehensive systematic review of realworld studies found few literature reviews on cardiovascular events [10]. Shah et al found more pronounced cardiovascular events in patients using AA than ENZ therapy [10]; however, some of the articles identified included research populations with pre-existing cardiovascular conditions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a comprehensive systematic review of realworld studies found few literature reviews on cardiovascular events [10]. Shah et al found more pronounced cardiovascular events in patients using AA than ENZ therapy [10]; however, some of the articles identified included research populations with pre-existing cardiovascular conditions [10]. By contrast, we excluded patients with pre-existing CVD to distinguish new cases of CVD from ongoing episodes and to make a stronger correlation that the identified cardiovascular events were due to the adverse effects of the medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that continued use of these drugs after transplantation increases the risk of cardiovascular disease and cancer, further decreasing transplant survival and death [ 9 ]. Cancer is the most prevalent complication in transplant recipients compared to other patients, which is associated with higher mortality rates and a reduced post-transplant survival rate [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%